Construction of pH-Sensitive Multifunctional Hydrogel with Synergistic Anti-Inflammatory Effect for Treatment of Diabetic Wounds - Xiaoyan Sun; Yan Li; Haifeng Wang; Yanqiu Meng; Xu Dai; Lina Du; Lei Li (Pharmaceutics)
Background/Objectives: A sustainable inflammatory response is a significant obstacle for diabetic wound care. In this study, the pH-sensitive multifunctional hydrogel ODex/BSA-Zn was fabricated via a Schiff base and coordination force for the first time. Methods: The hydrogel consisted of oxidized dextran (ODex), bovine serum albumin (BSA), and zinc ions (Zn2+) in the absence of an additional crosslinking agent. Results: The hydrogel showed excellent mechanical stability, fast self-healing ability, and significant anti-inflammatory effects, as demonstrated by the formation of dynamic covalent bonds between the aldehyde group (-CHO) of ODex and the amino group (-NH2) of BSA via the Schiff base reaction, as well as the metal-ion coordination reaction of Zn2+ with the imidazole ring of BSA. In a diabetic mouse full-thickness cutaneous defect wound model, the ODex/BSA-Zn hydrogel could effectively inhibit the inflammatory response and increase collagen deposition, thereby accelerating the transition of macrophage M1 to M2 and promoting wound closure. This study offers a promising therapeutic approach for managing long-term diabetic ulcers.